Too young for Cannabis? Choice of minimum legal age for legalized non-medical Cannabis in Canada - Hai V. Nguyen; Stephen Bornstein; John-Michael Gamble; Maria Mathews; Lisa Bishop; Shweta Mital (BMC, 2020)
Abstract Background Choice of minimum legal age (MLA) for cannabis use is a critical and contentious issue in legalization of non-medical cannabis. In Canada where non-medical cannabis was recently legalized in October 2018, the federal government recommended age 18, the medical community argued for 21 or even 25, while public consultations led most Canadian provinces to adopt age 19. However, no research has compared later life outcomes of first using cannabis at these different ages to assess their merits as MLAs. Methods We used doubly robust regression techniques and data from nationally representative Canadian surveys to compare educational attainment, cigarette smoking, self-reported general and mental health associated with different ages of first cannabis use. Results We found different MLAs for different outcomes: 21 for educational attainment, 19 for cigarette smoking and mental health and 18 for general health. Assuming equal weight for these individual outcomes, the 'overall' MLA for cannabis use was estimated to be 19 years. Our results were robust to various robustness checks. Conclusion Our study indicated that there is merit in setting 19 years as MLA for non-medical cannabis.